2020
DOI: 10.1038/s41598-020-68262-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Epsilon-Poly-l-lysine against phytopathogenic bacteria

Abstract: Antimicrobial peptides (AMps) are components of immune defense in many organisms, including plants. they combat pathogens due to their antiviral, antifungal and antibacterial properties, and are considered potential therapeutic agents. An example of AMp is epsilon-poly-l-lysine (epL), a polypeptide formed by ~ 25 lysine residues with known antimicrobial activity against several human microbial pathogens. EPL presents some advantages such as good water solubility, thermal stability, biodegradability, and low to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Cultures were maintained for up to 10 days at 28 • C in a rotary shaker at 200 rotations per minute. Samples to be analyzed by scanning electron microscopy (SEM) were prepared according to Rodrigues et al [91] and analyzed at CEMI, Unifesp, Brazil.…”
Section: Fastidiosa Strains and Growth Conditionsmentioning
confidence: 99%
“…Cultures were maintained for up to 10 days at 28 • C in a rotary shaker at 200 rotations per minute. Samples to be analyzed by scanning electron microscopy (SEM) were prepared according to Rodrigues et al [91] and analyzed at CEMI, Unifesp, Brazil.…”
Section: Fastidiosa Strains and Growth Conditionsmentioning
confidence: 99%
“…Remarkable abilities, such as edible, biocompatible, and broad (Ge et al, 2019); (B) The structure of EPL, one of the linear PLL forms; (C) Different molecular structure polylysine derivatives (Shi et al, 2015): (a) graft, (b) brush, (c) star architectures, (d) dendrimer, (e) hyperbranched, and (f) dendrigraft; (D) Self-assembled nanoparticles of PLL derivatives (Li Y. et al, 2020). antimicrobial spectrum, widen its application to fields, including food protection (Tuersuntuoheti et al, 2019), agriculture (Jiang et al, 2019;Rodrigues et al, 2020), and biomedical agents. Therefore, exploring the processing techniques and applications of EPL has attracted many concerns nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…With great biocompatibility and controllable yet numerous compositions, polyamino-acid, which consists of several kinds of amino acid residues, exhibits attractive properties ( Graphical Abstract ). Among different types of polyamino-acids, poly-L-lysine (PLL) has earned considerable attention in recent years, showing great performances in several areas, not only including areas like food preservation (Tuersuntuoheti et al, 2019 ) and environmental pollution treatment (Kwon et al, 2017 ; Bucatariu et al, 2020 ) but also been widely used in medical applications (Shukla et al, 2012 ; Shi et al, 2015 ; Rodrigues et al, 2020 ). The structure of these kinds of polymers could vary, including cycle, dendritic, α-linear, and ε-linear ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…However, food production can be affected by several factors, including pathogen attacks on host plants. Overall, it is estimated that, for many crops, potential loss caused by pathogens can reach over 30% of agricultural production worldwide (Yuliar et al, 2015;Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, natural/ synthetic antimicrobial molecules, as well as animal and vegetal biodiversity emerge as an immeasurable source of compounds with potential to control R. solanacearum strains. Some studies have shown that the essential oil extracted from Lantana camara and epsilon-poly-L-lysine (EPL), an antimicrobial peptide (AMP), inhibited bacteria growth (Cespedes et al, 2015;Mohamed et al, 2019;Rodrigues et al, 2020). These results can provide new antimicrobial substances, which are extremely important due to the current widespread of bacterial resistance (Datta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%